4,5-Dihydro-14-β-Hydroxy Scilladienolide-3-O-β-D-Glucopyranoside (AC-3) from the Stems of Milletia ovalifolia - Bose, Chandana; Chakrabarty, Ajita (Asian Journal of Chemistry, 2010)
The plant Millettia ovalifolia is commonly known as Gauj and belongs to the natural order Leguminosae. The stems of this plant are reported to be poisonous. The ethyl acetate soluble part of the concentrated alcoholic extract of stem when worked up by column chromatography yielded a novel cardenolide which was identified by chemical degradations, colour reactions and spectroscopic studies as 4,5-dehydro-14-β-hydroxy scilladienolide-3-O-β-D-glucopyranoside (AC-3).